Electrochemically assisted synthesis of three-dimensional FeP nanosheets to achieve high electrocatalytic activity for hydrogen evolution reaction. (13th September 2019) - Guo, Manman; Qu, Yaohui; Yuan, Cailei; Chen, Shu
Abstract: Iron phosphide (FeP) is a promising alternative catalyst for electrocatalytic hydrogen evolution reaction (HER) due to its low price, highly active catalytic sites and long-term anti-acid corrosion. Herein, we report a very facile strategy to fabricate novel FeP nanosheets as a HER electrocatalyst. Three-dimensional interconnected nanosheet structures of Fe2 O3 (3D Fe2 O3 NS) were directly exfoliated from metal Fe wires by alternating current (AC) voltage disturbance, and a simple subsequent phosphorization process could easily convert γ -Fe2 O3 into FeP phase, which also maintained the 3D NS structure. Importantly, increasing the AC voltage resulted in the evolution of iron-containing nanostructures from nanoparticles to 2D nanosheets until the formation of 3D NS structure. Owing to the large specific surface area, enriched active sites and abundant hierarchical porous channels, as-prepared 3D FeP NS has exhibited significantly enhanced electrocatalytic HER activities such as a cathode current density of 10 mA cm −2 at a small overpotential of 88 mV, low Tafel slope (47.7 mV dec −1 ) and satisfactory long-term stability in acidic electrolyte. We expect that this simple and green synthetic strategy of transition metal phosphides will provide a promising prospect to innovate nonprecious HER electrocatalysts. Graphical abstract: Efficient hydrogen evolution reaction electrocatalyst electrodes based on 3D FeP nanosheets achieved by electrochemical exfoliation coupling with phosphorization process.Image 1 Highlights: Three-dimensional FeP nanosheets were facilely synthesized. This novel synthetic process involved in direct exfoliation in a blank alkaline solution. The FeP electrocatalyst showed excellent HER activity with 10 mA cm −2 at 88 mV overpotential. HER activities were mainly ascribed to stable 3D NS structure and enriched active sites.